DEVELOPMENT AND MANAGEMENT OF SUPPORT SYSTEM FOR EARLY SCHOOL LEAVERS - Krage, Gunta; Ivanova, Ilze (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The started education reform School 2030 in Latvia requires to implement essential changes in approaches to education. The content and the way of learning, how the teachers manage everyday teaching and learning are being revised starting from kindergarden to the graduating of the school.The vision of the student includes the active and mindful participation of everybody in the life of the society, has deepened the necessary knowledge,developed skills and attitudes to be useful for the society. It means that the accent is put on every child to be involved in education.Education has to be built on equity, equality and quality. At the same time there is a great discrepancy between reality and aim of education in Latvia. There is a quite big drop out of students from general and professional education.According to the research of Baltic social research institute (2014) 26% of students from secondary schools and gymnasiums leave school before graduating it. Schools have a great potential to prevent it.The authors discuss the opportunity to develop support system in general education schools to prevent and avoid drop out of learning. The great attention is being paid to the cooperation and collaboration in the system of education, development of teachers’ competences.